Cellular production of a counterfeit viral protein confers immunity to infection by a related virus - Warner, Benjamin E.; Ballinger, Matthew J.; Yerramsetty, Pradeep; Reed, Jennifer; Taylor, Derek J.; Smith, Thomas J.; Bruenn, Jeremy A. (PeerJ (San Francisco, CA), 2018)
DNA copies of many non-retroviral RNA virus genes or portions thereof (NIRVs) are present in the nuclear genomes of many eukaryotes. These have often been preserved for millions of years of evolution, suggesting that they play an important cellular function. One possible function is resistance to infection by related viruses. In some cases, this appears to occur through the piRNA system, but in others by way of counterfeit viral proteins encoded by NIRVs. In the fungi, NIRVs may be as long as 1,400 uninterrupted codons. In one such case in the yeast Debaryomyces hansenii , one of these genes provides immunity to a related virus by virtue of expression of a counterfeit viral capsid protein, which interferes with assembly of viral capsids by negative complementation. The widespread occurrence of non-retroviral RNA virus genes in eukaryotes may reflect an underappreciated method of host resistance to infection. This work demonstrates for the first time that an endogenous host protein encoded by a gene that has been naturally acquired from a virus and fixed in a eukaryote can interfere with the replication of a related virus and do so by negative complementation.